Does Bariatric Binge‐Eating Size Matter? Conceptual Model and Empirical Support. Issue 9 (29th July 2020) - Ivezaj, Valentina; Lydecker, Janet A.; Wiedemann, Ashley A.; Duffy, Andrew J.; Grilo, Carlos M.
Abstract : Objective: Bariatric surgery affects the quantity of food individuals can eat, yet some individuals still experience loss of control (LOC) while eating. This cross‐sectional study examined a new classification system for binge/LOC eating following bariatric surgery. Methods: A total of 168 individuals who underwent bariatric surgery 6 months earlier and reported LOC eating were administered the Eating Disorder Examination–Bariatric Surgery Version interview and self‐report measures of depressive symptoms, functional impairment, and physical and mental health‐related quality of life. Three groups were created based on the largest LOC‐eating episode determined by the Eating Disorder Examination–Bariatric Surgery Version interview as follows: (1) "traditional" objective binge‐eating episodes, defined as eating unusually large quantities of food while having LOC; (2) "bariatric‐objective binge eating, " meaning unusually large quantities for postsurgical bariatric patients with LOC; and (3) "bariatric‐subjective binge eating, " meaning small quantities of food with LOC after surgery. Results: In total, 75% ( n  = 126) met criteria for the bariatric‐objective binge episodes group, 10% ( n  = 17) met criteria for the traditional objective binge‐eating group, and 15% ( n  = 25) met criteria for the bariatric‐subjective binge episodes group. The three groups differed significantly, with a graded pattern by binge size, in global eating‐disorder psychopathology, depressive symptoms, and functional impairment but not quality of life. Conclusions: These findings provide empirical support for a new classification system for bariatric binge/LOC eating. Binge size was associated with distinct psychopathology. Longitudinal follow‐up is needed to ascertain effects on clinical outcomes.